Allamah Jawadi Amuli and the Necessary Cognitions in Spiritual Wayfaring - Muhammad Javad Rudgar (حکمت اسرا)
The paper discusses the situation and role of cognition in a wayfarer’s spiritual journey. The argument is presented with a focus on Allamah Javadi’s views on this subject which are based primarily on the Unity of God and the Right Path and the concept of wilayah in the Shari’a and Shi’a Islamic thought. Having examined his view, the paper attempts to criticise false mysticism in its Various forms and how they are derived from genuine practical mysticism.